2017
DOI: 10.1186/s13104-017-2409-z
|View full text |Cite|
|
Sign up to set email alerts
|

Protective effect of Curcuma longa L. extract on CCl4-induced acute hepatic stress

Abstract: BackgroundThe Curcuma longa L. (CLL) rhizome has long been used to treat patients with hepatic dysfunction. CLL is a member of the ginger family of spices that are widely used in China, India, and Japan, and is a common spice, coloring, flavoring, and traditional medicine. This study was performed to evaluate the hepatoprotective activity of CLL extract and its active component curcumin in an acute carbon tetrachloride (CCl4)-induced liver stress model.MethodsAcute hepatic stress was induced by a single intrap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 42 publications
6
32
0
1
Order By: Relevance
“…Although no studies have evaluated the effects of CL feeding following stress induced by oral gavage even in the absence of toxic agents, Evidence-Based Complementary and Alternative Medicine the decline observed could be associated with the consequence of less availability of free radicals or superoxide radicals (substrate for these antioxidant enzymes), which decreased gradually after administration of CL. It could be due to the reported potent superoxide radical-scavenging property of CL, which has been shown to be as effective as e findings of this trial are consistent with a previous study that demonstrated how prior treatment with CL roots resulted in a reduction in the levels of lipid peroxidation and oxidative stress [21]. Other studies reported similar results, in which oral administration effectively induced an increase in quinone reductase and glutathione transferase activity, even in the absence of toxic agents.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although no studies have evaluated the effects of CL feeding following stress induced by oral gavage even in the absence of toxic agents, Evidence-Based Complementary and Alternative Medicine the decline observed could be associated with the consequence of less availability of free radicals or superoxide radicals (substrate for these antioxidant enzymes), which decreased gradually after administration of CL. It could be due to the reported potent superoxide radical-scavenging property of CL, which has been shown to be as effective as e findings of this trial are consistent with a previous study that demonstrated how prior treatment with CL roots resulted in a reduction in the levels of lipid peroxidation and oxidative stress [21]. Other studies reported similar results, in which oral administration effectively induced an increase in quinone reductase and glutathione transferase activity, even in the absence of toxic agents.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies also reported similar findings that CL rhizome extract increased the activity of SOD, GPx, and CAT enzymes [23]. Also, oral administration of aqueous extract of CL rhizomes did not cause significant changes in liver function, demonstrated by hepatic enzymes levels and histopathological changes in liver tissue [21,23]. e current study showed that six days of 100 mg/kg CL (P.O.)…”
Section: Discussionsupporting
confidence: 85%
“…These findings are supported by previous studies. [20][21][22][23][24][25] Singh et al 26 also reported similar histological findings. The present study has a few limitations such as the; inflammatory markers and antioxidant enzymes were not analyzed due to funding issues.…”
Section: Photomicrograph-4 Liver Injury Is Decreased (Central Venulementioning
confidence: 72%
“…These findings indicated that EECL has protective effects against CCl 4 -induced hepatotoxicity in rats via antioxidant activities and phase II detoxifying enzymes (Lee et al, 2010). EECL has also been reported to exhibit protective effects in liver injury due to the treatment of CCL 4 through increasing levels of antioxidants enzymes of SOD, glutathione peroxidase activity, and glutathione content in the CCl 4 -treated group (p<0.05), leading to a reduced lipid peroxidase level (Lee et al, 2017). C. longa extract at the concentration of 0.5% given to Sprague Dawley rats also revealed the antioxidant activity in vivo.…”
Section: In Vivo Antioxidant Activities Of Curcuma Longamentioning
confidence: 79%